Wetland archaeology and the impact of climate change. (December 2022) - Matthiesen, Henning; Brunning, Richard; Carmichael, Bethune; Hollesen, Jørgen
Abstract: Abstract : Wetland archaeological sites offer excellent but vulnerable preservation conditions. This article presents examples of threats to such sites that may be enhanced, or diminished, by climate change, discusses methods for predicting and quantifying impacts, and examines what heritage managers can do to mitigate their effects. The consequences of climate change for wetland archaeological sites are likely to be severe and widespread but hard to predict and with significant local variation. At the same time, wetlands are increasingly acknowledged for their ability to sequester carbon and to mitigate climate change, prompting an increased focus on their protection that may also benefit wetland archaeology.